To What Extent Is White-Collar Crime Understandable? An Empirical Study of Determinants Based on the Theory of Convenience - Gupta, Chander Mohan (Crime & delinquency, 2025)
White-collar crimes (WCC) or financial crimes (FC) are the crimes that are linked with the top-level management representatives who are responsible to make the right decisions for the better functioning of the organization, these individuals are highly respectable as they hold a position of high repute. However, when the same individuals either under the pressure of performance or personal issues misuse the power and control vested on them due to the position they hold in the organization, take certain decisions which lead the organization into jeopardy. These individuals not only put the hard-earned money of the investors on stake but also enjoy the best of the facilities on the basis of their position. In the said article the authors have tried to answer two major questions regarding the abuse of position and manipulation of the financial statements at the struggling phase of the firm. The base of the study is convenience theory which was used to understand the concept of convenience theory for which a questionnaire based on 7-point Likert scale was used in which responses of 230 MBA students were studied. The results were near to what were expected supporting the fact that individuals are misusing their position to commit WCC, supporting the concept of convenience theory being used in the study.